Milena Melfi and Olympia Bobou (eds) Hellenistic Sanctuaries between Greece and Rome. - Spawforth, A. J. S. (Journal of Greek Archaeology, 2019)
This volume deals with the period from 300 BC to AD 100. The sixteen chapters, all in English, arise from an Oxford conference in September 2010 taking the post-Classical polis sanctuary in Greece, Sicily and Magna Graecia as its focus. The main disciplinary emphasis is on classical archaeology and art; two chapters (Yves Lafond; Maria Kantirea) foreground epigraphy; another includes an excavator’s unpublished note revealing a new inscription about Damophon of Messene (Melfi in the second of her three contributions). The chapters are not grouped thematically, although two sub-divisions stand out: one dealing with broader topics and regions, and the other focused on a particular polis or sanctuary.